The tragic and non-tragic cultures, or Yaichiemon’s riddle - Korusiewicz, Maria (Folia Philosophica, 2002)
The present article is an attempt to describe the cultural determinants of the categoryof tragicality, the determinants considered in relation to the very generally conceived cultural systems of the West and East (particularly the Anglo-European tradition, on the one hand, and the Japanese and Chinese ones, on the other, as the most characteristic for the discussed problem). The particular parts of the article concentrate on various differences in approaching the notions of transcendence, individualism, natural and normative law. Summing up, the author makes a list of the features conditioning, in a given culture, the development of a tragic consciousness that influences the formation of a specific vision of the universe.